An Overview Knowledge and Usage of Herbal Medicines during The COVID-19 Pandemic by Students of Poltekkes Kemenkes Jakarta II - Nanang Kurnia Achmadi; Yayan Setiawan; Aprilia Ayu Purwati (Politeknik Kesehatan Kemenkes Jakarta II, 2021)
COVID-19 has now become a global health problem. In Indonesia, there are 828.026 confirmed cases as of January 10, 2021.(1) To deal with this current situation, prevention efforts are needed. One of them increases endurance by using herbal remedies. In addition to having been used for generations, several studies have shown that herbal medicines have the potential to increase endurance.The purpose of this study was to describe the knowledge and usage of herbal medicines during the COVID-19 pandemic.This study using the purposive sampling method with one hundred respondents. Data were collected based on primary data using a google form questionnaire with univariate analysis. On Preliminary results are Most of respondents had pretty good knowledge in forty eight point eight percent, and jamu on sixty nine point five percent as the herbal medicine of choice, when pharmacies to get herbal medicines. Moreover, the implications are the knowledge of using herbal medicine during the COVID-19 pandemic is good and Jamu is the most used herbal medicine based of the types. This research will be continued with more samples to better represent the conclusions. Keywords: Knowledge, Usage, Herbal Medicines